KRITIK RADIKALISME PEMIKIRAN HTI: Studi Kontekstualitas Matan Hadis-Hadis Khilafah - Nasrulloh Nasrulloh (UIN Siber Syekh Nurjati Cirebon, 2019)
This paper is an academic step to discover a scientific fact through the study of hadith texts that legitimize the ideological truth of the HTI group. In generating radical thoughts, the HTI group has a main reference, a book entitled Nizam al-Hukm fiÂ al-Islam, written by the founder of Hizb al-Tahrir, Taqiyuddin al-Nabhani. In this study, the themes of the hadiths discussed are those related to the khilafah (caliphs) contained in the book and in the sub-chapter of Al-Khilafah (the Caliphate). The book was chosen because it is the main reference book of HTI that cites hadiths which are textually radical. Some key points that become the objectives of this study are: (1) What is the status of the authenticity of khilafahÂ hadiths?, (2) How is the contextual understanding of khilafah hadiths?, and (3) What are the implications of HTI's understanding of khilafah hadiths in the context of the Unitary State of the Republic of Indonesia?